Architecture at the End of the Earth : Photographing the Russian North - Brumfield, William Craft, 1944- (Book collections on Project MUSE., 2015)
Carpeted in boreal forests, dotted with lakes, cut by rivers, and straddling the Arctic Circle, the region surrounding the White Sea, which is known as the Russian North, is sparsely populated and immensely isolated. It is also the home to architectural marvels, as many of the original wooden and brick churches and homes in the region's ancient villages and towns still stand. Featuring nearly two hundred full color photographs of these beautiful centuries-old structures, Architecture at the End of the Earth is the most recent addition to William Craft Brumfield's ongoing project to photographically document all aspects of Russian architecture.